2020
DOI: 10.1002/alr.22536
|View full text |Cite
|
Sign up to set email alerts
|

Impact of induction chemotherapy and socioeconomics on sinonasal undifferentiated carcinoma survival

Abstract: BackgroundSinonasal undifferentiated carcinoma (SNUC) is an uncommon malignancy of the nasal cavity and accessory sinuses with limited available studies evaluating role of induction chemotherapy (IC), demographics, and socioeconomic factors on overall survival (OS).MethodsThe 2004‐2015 National Cancer Database was queried for patients with histologically confirmed SNUC. IC was defined as chemotherapy administered 6 months to 2 weeks before surgery or ≥45 days before radiotherapy.ResultsOf 440 identified patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…However, only two patients received concomitant RT + CT and the other six RT (combined with surgery in two cases). This outcome corroborates findings by Lehrich et al, in a study involving 440 patients, indicating that induction chemotherapy may not provide survival benefits in SNUC patients [20]. As for many other subsets of SNM, further studies are warranted also for SNUC.…”
Section: Discussionsupporting
confidence: 89%
“…However, only two patients received concomitant RT + CT and the other six RT (combined with surgery in two cases). This outcome corroborates findings by Lehrich et al, in a study involving 440 patients, indicating that induction chemotherapy may not provide survival benefits in SNUC patients [20]. As for many other subsets of SNM, further studies are warranted also for SNUC.…”
Section: Discussionsupporting
confidence: 89%
“…When treating head and neck cancers, radiotherapy is often employed, either alone or in combination with surgery [5][6][7][8]. In order to reduce normal tissue toxicity, the use of intensity-modulated radiotherapy has been implemented [9].…”
Section: Introductionmentioning
confidence: 99%
“…A large study on adult pituitary surgery outcomes using the national inpatient sample found that black patients and patients with Medicaid insurance were significantly more likely to have a postoperative complication compared to white patients and patients with private insurance 20 . Another study of patients with sinonasal undifferentiated carcinoma reported significantly worse overall survival outcomes in patients with government insurance or low education 21 . Based on these findings, as well as findings from other studies reported in head and neck oncology literature, 22–24 it is plausible that low socioeconomic status might drive the racial disparity observed in our sample.…”
Section: Discussionmentioning
confidence: 99%